2014
DOI: 10.1016/j.nlm.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Towards a better understanding of cognitive behaviors regulated by gene expression downstream of activity-dependent transcription factors

Abstract: In the field of molecular and cellular neuroscience, it is not a trivial task to see the forest for the trees, where numerous, and seemingly independent, molecules often work in concert to control critical steps of synaptic plasticity and signalling. Here, we will first summarize our current knowledge on essential activity-dependent transcription factors (TFs) such as CREB, MEF2, Npas4 and SRF, then examine how various transcription cofactors (TcoFs) also contribute to defining the transcriptional outputs duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 109 publications
1
18
0
Order By: Relevance
“…This behavior resembles the behavior in CREBBP mutated individuals [Galera et al, ; Yagihashi et al, ; Waite et al, ], especially with respect to the obsessive‐compulsive behavior and occurrence of anxieties. Likely, the behavior can be explained directly by the disturbed function of the P300 protein [Nonaka et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…This behavior resembles the behavior in CREBBP mutated individuals [Galera et al, ; Yagihashi et al, ; Waite et al, ], especially with respect to the obsessive‐compulsive behavior and occurrence of anxieties. Likely, the behavior can be explained directly by the disturbed function of the P300 protein [Nonaka et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we identified two hippocampal genes, the brain‐specific activity‐dependent transcription factor Npas4 (neuronal Per‐Arnt‐Sim domain protein 4) and the immediate early gene Arc (activity‐regulated cytoskeleton‐associated protein), as being differentially expressed with ageing, cognitive decline and 11β‐HSD1 deficiency. Given the crucial roles of Npas4 and Arc in the regulation of learning and memory , and their decreased mRNA levels in the hippocampus of aged memory‐impaired (AI) but not unimpaired (AU) wild‐type or 11β‐HSD1‐deficent mice, it is suggested that these proteins may lie in pathways that are important for the preservation of hippocampus‐associated memory in ageing and are maintained by 11β‐HSD1 deficiency/inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…protein), as being differentially expressed with ageing, cognitive decline and 11b-HSD1 deficiency. Given the crucial roles of Npas4 and Arc in the regulation of learning and memory (31,(33)(34)(35)(36)(37), and their decreased mRNA levels in the hippocampus of aged memoryimpaired (AI) but not unimpaired (AU) wild-type or 11b-HSD1-deficent mice, it is suggested that these proteins may lie in pathways that are important for the preservation of hippocampus-associated memory in ageing and are maintained by 11b-HSD1 deficiency/inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms that precisely regulate gene target specificity dictate changes in the complement of neuronal proteins and, ultimately, such critical fates as whether neurons live or die, and whether synaptic connections are appropriately strengthened, weakened, or eliminated during processes such as information storage. Signaling cascades triggered downstream of neuronal activity by neurotransmitters, growth factors, and cytokines can individually and cooperatively induce multiple activity-responsive transcription factors, including CREB, Npas4, MEF2, MeCP2 (Nonaka et al, 2014), and nuclear factor-kappaB (NF-κB) (Shrum and Meffert, 2008). How these discrete transcription factors contribute unique or overlapping functions to disambiguate incoming signals and to orchestrate context appropriate changes in gene expression remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%